The effect of rosella tea on weight loss among overweight women in Yogyakarta, Indonesia: An interventional pilot study - Mayasari, Noor Rohmah; Aline, Sabrina; Hadi, Novian Swasono (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: Rosella tea is an anthocyanin-rich herbal remedy known to have an anti-obesity effect. Overweight women are expected to lose weight by consuming herbal tea without improving their lifestyles.Objectives: This pilot study evaluated the effects of rosella tea on reducing body weight among overweight women without improving their lifestyle.Materials and Methods: A quasi-experimental design pre-post intervention was used in this study. Twenty-three overweight women aged 30-60 years were involved. The control and treatment groups consisted of twelve and eleven respondents, respectively. The treatment group consumed ± 250 ml rosella tea twice a day for 14 days. During the study, both groups were instructed to not change their lifestyles. Paired t-test and independent t-test were performed to test the effect of rosella tea consumption within and between groups, respectively.Results: After 14 days of consumption of rosella tea, the body weight was decreased by - 0.15 ± 0.24 kg (from 63.5 ± 10.35 kg to 63.35 ± 10.33 kg) for the treatment group and - 0.21 ± 0.25 (from 64.65 ± 9.54 kg to 65.65 ± 9.99 kg) for the control group but the difference did not reach significant levels (p>0.05). In both groups, dietary intake (e.g., calorie, carbohydrate, protein, and fat) and sedentary behaviour in the initial study were not different compared to at the end of the study, except for the lesser extent of dietary fibre in the control group.Conclusion: Administration of rosella tea for 14 days did not induce weight loss in overweight women without any lifestyle improvement (increase dietary fibre).